Analisis Antioksidan Cookies Subtitusi Terpung Jewawut (Foxtail Millet) dan Tepung Bekatul sebagai Sumber Energi Protein untuk Balita Underweight: Antioxidant Analysis of Cookes Subtitutrd with Barley Flour (Foxtail Millet) and Rice Bran Flor: A source of Protein Energy for Underweight Toddlers - Nabilah Azka Tzaniyah; Safrullah Amir; Abdul Salam; Nurhaedar Jafar; Zaenal (Jurnal Diskursus Ilmiah Kesehatan, 2023)
Background: Underweight is one of the major nutritional problems in Indonesia. In order to address nutrition issues, the government issued Presidential Instruction No. 1 on Supplementary Feeding in 1997. Foxtail millet is one of the crops with the potential to be developed as a source of carbohydrates to replace rice in order to strengthen food security. Food security as a carbohydrate source to replace rice. Rice bran and Foxtail Millet has the potential to contribute to Indonesia's food security. Aims: This study aims to determine the presence of antioxidant compound activity compounds qualitatively. Methods: This is a descriptive laboratory-based study. Laboratory examination includes screening for flavonoid, phenolic, and tannin compounds based on the selected formula that has been tested for acceptability, namely F17. Cookies will be extracted using methanol and tested with color change indicators using several reagents to determine the presence of flavonoids, phenolic compounds, and tannin compounds. Antioxidant activity was tested with the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Results: The results showed that flavonoid, phenolic, and tannin compounds were detected in the cookie extract. As for antioxidant activity, it is categorized as moderate, with an IC50 value of 119.55 ppm. Conclusion: Through this study, it can be concluded that cookies substituted with Foxtail millet and Bran Rice flour have moderate antioxidant activity and contain several phytochemical compounds.